Island and The Construction of a Maritime Boundary: Pushing The Limits of State Sovereignity - Rouche, Isabelle (UI Scholars Hub, 2018)
Islands play a crucial role in fixing the limits of the States’ sovereignty over maritime spaces as they can considerably distort the final delimitation line. However, islands often give rise to controversy and most of the contentious cases have entailed major problems and divergence of views as the proper impact of islands on the construction of a boundary line. The maritime delimitation case law provides practitioners and States with a wide variety of scenario that deprives the law on this issue from transparency, coherence and predictability. The aim of this paper is to give a comprehensive approach of the influence of islands in the construction of a maritime boundary. Indeed, a thorough analysis of the case law, including the most recent, reveals that international judges or arbitrators have - rightly so - chosen a conservative approach, consisting in attributing a largely secondary role to these features. Interestingly, a categorization of the methods of adjustment of boundary lines can now be convincingly identified depending on their status (insular States, accessory islands, archipelagic islands, constitutive islands etc.).